(untitled) (Zoological Records and Reviews, 2025)
The Netherlands has a distinctive and historically rich tradition of zoological research, from the pioneering natural history collections of the 17th century to the development of ethology as a formal scientific discipline and contemporary contributions to molecular ecology, conservation genetics, and multi-taxon biodiversity monitoring. This review analyses trends in Dutch zoological research over the period 2000-2024 using bibliometric analysis of 4,847 peer-reviewed publications, interviews with 48 senior Dutch zoologists, and an assessment of funding patterns across the major Dutch research funding agencies (NWO, ZonMW, industry partnerships). Publication output in Dutch zoology grew at 4.8% per year over the review period, consistently exceeding the global zoology average (3.2% per year), with a compound growth rate of 168% over 25 years. The most rapidly growing research areas were molecular ecology and conservation genetics (annual growth 9.4%), citizen science and biodiversity informatics (8.8%), and applied conservation biology (7.2%). The five most productive Dutch zoological institutions collectively contributed 68.4% of all publications. International collaboration intensity increased from 42.4% to 74.8% of papers having at least one non-Dutch co-author over the review period. Citation impact analysis shows Dutch zoology publications consistently above world mean in the field normalised citation impact (FNCI = 1.48 +- 0.12 for 2015-2024), confirming high research quality. Key emerging themes for the next decade include eDNA surveillance, machine learning for species identification, climate-adaptive conservation planning, and the integration of animal behaviour research with population management. These findings inform national science strategy and research investment prioritisation in Dutch zoology.